Cooperative security: NATO's partnership policy in a changing world - Trine Flockhart (Danish Institute for International Studies (DIIS), 2014)
In this DIIS Report, Trine Flockhart (editor) brings together security researchers and practitioners with in-depth expertise on NATO and NATO's partnerships. The aim is to focus on NATO's new partnership policy and on the role and meaning of the new concept, 'cooperative security'. Overall the report argues that NATO's approach to partnership should be seen as an essential component of a wider grand strategy to sustain a rule based liberal order in the 21st century. Each chapter of the report hones in on a particular aspect of the new partnership policy and/or the concept 'cooperative security' or it presents a particular national or regional perspective. With a few exceptions, the report is based on papers presented and discussed at a conference held at DIIS in June 2013 in cooperation between DIIS and the Centre for War Studies at University of Southern Denmark.
Keywords: 300